Obstacles to Attract Foreign Investment in Light of the Saudi Vision 2030: An Analytical Study - Mbarki, Mohamed Ali Hadi (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the obstacles to attract foreign investments in light of the Saudi vision 2030. The study used the descriptive analytical approach, and both the study population and sample represented in foreign investments and its obstacles that depend on the phenomenon as they exist in light of the Saudi vision 2030. The study also showed the changes brought about by the Saudi vision 2030 to attract investments and the extent of solutions developed by the Saudi vision 2030 to eliminate these obstacles. The study concluded that the Saudi vision 2030 developed a specific objective for foreign investment, which is to reach 5.7% of the Gross Domestic Product (GDP). As well, the study found that the Saudi vision 2030 seeks that Kingdom of Saudi Arabia shall become among the 15 largest economies in the world by 2030. As for the Global Competitiveness Index (GCI), Kingdom of Saudi Arabia aims to increase its position to become among the top 10 countries in the world. The study recommended the necessity of continuing to implement the Saudi vision 2030 until achieving its desired economic objectives for which the vision was set, as well as the need to make a periodic evaluation of the vision and the extent of its application and its functioning according to the plan set for implementation to know the size of the change taking place at the economic level.